1987
DOI: 10.1111/j.1365-2125.1987.tb03120.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of diuretics and ACE inhibitors, their renal and antihypertensive actions‐parallels and contrasts.

Abstract: 1 The emergence of diuretic drugs and angiotensin converting enzyme (ACE) inhibitors ranks amongst the major therapeutic advances of modern medicine. The discovery of these drug groups arose largely by chance, yet each has dramatically influenced the treatment of congestive cardiac failure and arterial hypertension. 2 The central role which diuretics have had in the management of both oedema and hypertension hinges on their ability to induce a net renal excretion of solute and water by selective interference w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…However, changes in ECC do not necessarily reflect an influence of cilazapril on glomerular filtration rate since tubular secretion of creatinine may be influenced by ACE inhibitors (Bauer & Reams, 1985). In accordance with the known natriuretic properties of calcium antagonists (Zanchetti & Leonetti, 1985;Sluiter et al, 1987b) and ACE inhibitors (Lant, 1987;Todd & Heel, 1986) we observed a slight reduction in body weight during nitrendipine, cilazapril, and during the combination of these two drugs. In our study dry cough was the most important side effect observed during cilazapril.…”
Section: Discussionsupporting
confidence: 64%
“…However, changes in ECC do not necessarily reflect an influence of cilazapril on glomerular filtration rate since tubular secretion of creatinine may be influenced by ACE inhibitors (Bauer & Reams, 1985). In accordance with the known natriuretic properties of calcium antagonists (Zanchetti & Leonetti, 1985;Sluiter et al, 1987b) and ACE inhibitors (Lant, 1987;Todd & Heel, 1986) we observed a slight reduction in body weight during nitrendipine, cilazapril, and during the combination of these two drugs. In our study dry cough was the most important side effect observed during cilazapril.…”
Section: Discussionsupporting
confidence: 64%
“…Although it took close to 40 years from the discovery of the clinical effectiveness of organomercurials as diuretics to the arrival of the first orally active diuretic chlorothiazide, it took only 5 years (1971-1976) to succeed in developing an oral ACE inhibitor as a successor to the parenterally effective nonapeptide ACE inhibitor teprotide [2]. The first orally active ACE inhibitor was the drug captopril, which was commercially released in 1981.…”
Section: History Of Ace Inhibitorsmentioning
confidence: 99%
“…27 Diuretics are believed to lower BP generally by stimulation of diuresis-natriuresis, resulting in reduction of plasma fluid, extracellular fluid volume, and sodium. 19,28 Long-term diuretic therapy is also associated with a reduction in total peripheral resistance of unclear mechanism, contributing to its antihypertensive effect. 19,28 The main physiologic basis for adding a diuretic to an ACE inhibitor is that the sodium depletion induced by the diuretic will trigger counterregulatory activation of the RAS that will make BP more dependent on angiotensin II, and thus potentiate the efficacy of the ACE inhibitor.…”
Section: Optimal Combinations Of Antihypertensive Drugs Typically Invmentioning
confidence: 99%
“…19,28 Long-term diuretic therapy is also associated with a reduction in total peripheral resistance of unclear mechanism, contributing to its antihypertensive effect. 19,28 The main physiologic basis for adding a diuretic to an ACE inhibitor is that the sodium depletion induced by the diuretic will trigger counterregulatory activation of the RAS that will make BP more dependent on angiotensin II, and thus potentiate the efficacy of the ACE inhibitor. 29,30 The blunting of this counterregulatory response with ACE inhibition, particularly the inhibition of aldosterone release, also enhances the antihypertensive efficacy of the diuretic.…”
Section: Optimal Combinations Of Antihypertensive Drugs Typically Invmentioning
confidence: 99%
See 1 more Smart Citation